Mourning a breast - Xi, Xi (New York Review Books classics., 2024)
"By Xi Xi, part of the first generation of writers raised in Hong Kong, a wise and amiably written book of autobiographical fiction on the author's experience with breast cancer-from diagnosis to treatment to recovery-and her passage from a life lived through the mind into a life lived through the body. In 1990, the Hong Kong cult classic writer Xi Xi was diagnosed with breast cancer and began writing in order to make sense of her diagnosis and treatment. Mourning a Breast, published two and a half years later, is a disarmingly honest and deeply personal account of the author's experience of a mastectomy and of her subsequent recovery. The book opens with her gently rolling up a swimsuit. A beginning swimmer, she loves going to the pool, eavesdropping on conversations in the changing room, shopping for swimsuits. As this routine pleasure is revoked, the small loss stands in for the greater one. But Xi Xi's mourning begins to take shape as a form of activism. In a conversational, even humorous, manner, she describes her previous blinkered life of the mind before she came into her body and learned its language. Addressing her reader as frankly and unashamedly as an old friend, she coaxes and confesses, confronts society's failings, and advocates for a universal literacy of the body. Mourning a Breast was heralded as the first Chinese language book to cast off the stigma of writing about illness and to expose the myths associated with breast cancer. A radical and generous book about creating in the midst of mourning"--